Adaptive variable-structure finite-time mode control for spacecraft proximity operations with actuator saturation. Issue 10 (15th May 2017) - Lee, Daero; Vukovich, George; Gui, Haichao
Highlights: An adaptive variable-structure finite-time control is developed. No prior knowledge of inertia matrix and mass of the spacecraft is required. Finite-time convergence of the feedback system is established. Abstract: This paper presents an adaptive variable-structure finite-time control for spacecraft proximity maneuvers under parameter uncertainties, external disturbances and actuator saturation. The coupled six degrees-of-freedom dynamics are modeled for spacecraft relative motion, where the exponential coordinates on the Lie group SE(3) are employed to describe relative configuration. No prior knowledge of inertia matrix and mass of the spacecraft is required for the proposed control law, which implies that the proposed control scheme can be applied in spacecraft systems with large parametric uncertainties in inertia matrix and mass. Finite-time convergence of the feedback system with the proposed control law is established. Numerical simulation results are presented to illustrate the effectiveness of the proposed control law for spacecraft proximity operations with actuator saturation.